THU0202 INTERFERON STIMULATED GENE 15 PROTECTS REGULATORY T CELL OF SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS FROM INTERFERON ALPHA-MEDIATED DEPLETION. (June 2019) - Spinelli, Francesca Romana; Pacella, Ilenia; Piconese, Silvia; Ceccarelli, Fulvia; Miranda, Francesca; Alessandri, Cristiano; Barnaba, Vincenzo; Valesini, Guido; Conti, Fabrizio
Abstract : Background: Data on T regulatory (T reg) cells number and functions in patients with Systemic Lupus Erythematosus (SLE) are conflicting (1). Type I interferon (IFN) decreases Treg proliferation and induces Treg apoptosis (2). IFN stimulated gene 15 (ISG15) is an IFN-induced protein with a negative effect on IFN pathway. Objectives: Aim of the study was to evaluate the effect of IFN alpha and ISG15 on Treg number and on STAT1 phosphorilation in patients with SLE. Methods: We recruited patients with SLE classified according to 1997 ACR criteria. We collected demographic and clinical data including disease duration, disease activity scored according to Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) 2K. Peripheral blood mononuclear cells (PBMC) were isolated from whole blood samples. Intracellular phosphorilated STAT1 (pSTAT) levels were evaluated in Treg (CD4+FOXP3+CD127 low cells) and conventional T cell (Tconv, CD4+FOXP3- cells) by multiparametric flow cytometry, ex vivo or after stimulation with recombinant IFN alpha. PBMC were cultured for 48 hours with anti-CD3 or anti-CD3 and IFN alpha; the frequency of Treg was analysed by multiparametric flow cytometry. ISG15 mRNA expression was evaluated by RT-PCR on PBMC from SLE patients. Data were expressed as mean ± standard deviation or median (interquartile range(according) to the distribution; Mann-Whitney and Spearman tests were applied. P value <0.05 were considered statistically significant. Results: We enrolled 21 SLE patients [F:M 20:1; mean age 45.2 ± 12.9 years; mean disease duration 157.5± 103 months; median SLEDAI 2(4)] Overall, median baseline ISG15 mRNA expression was 0.06 (IQR 0.16); patients were divided into ISG15-high (n=9) and ISG15-low (n=12), according to the mean mRNA expression. Ex vivo, after short-term treatment with IFN alpha (15 and 25 minutes), we observed a significant increase in STAT1 phosphorilation compared to baseline both in Treg and Tconv (p<0.00001), in ISG15-high and ISG15-low patients (Figure 1 A and B ); however, high ISG15 levels protect both Treg and Tconv from STAT1 phosphorilation (Figure 1 C ). After 48 of colture with IFN alpha, we observed a decrease in Treg and Tconv number, significantly greater in ISG15-low cells (Figure 1D ). Treg frequency and ISG15 expression in Treg were higher in active vs inactive SLE patients [SLEDAI > 4 vs SLEDAI <4] (p<0.05). Conclusion: ISG15 protects T conventional cells from STAT1 phosphorilation and induces resistance to T regulatory cells depletion. The results of the study suggest that ISG15, a protein induced by IFN in the acute phase of the disease, exerts a negative feedback, allowing the recovery of T reg. References: [1] Zhang SX, et al. J Immunol res. 2018 [2] Piconese S, et al. Cytokine Growth Factor rev. 2014 Disclosure of Interests: None declared